2016
DOI: 10.1097/md.0000000000002348
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oral Hygiene Maintenance on the Association Between Periodontitis and Osteoporosis

Abstract: Both periodontitis and osteoporosis have similar sign of bone resorption in nature. However, the relationship of the severity between these 2 bone-loss diseases is still uncertain.The aim of this study was to investigate the association between the severity of osteoporosis and periodontitis regarding the impact of oral hygiene maintenance. In total, 35,127 osteoporosis patients and 50,498 comparisons were derived from the Longitudinal Health Insurance Database of Taiwan between 2000 and 2010. The population wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 25 publications
2
31
0
2
Order By: Relevance
“…However, the periodontal assessment in those studies was alveolar bone loss, and oral hygiene was not evaluated. The effect of oral hygiene on the association between BMD and periodontal disease was evaluated in previous cross‐sectional studies with diverse findings . Similar to our findings, the Buffalo Women's Health Initiative Observational Study reported a significant association between skeletal BMD and the mean CAL in postmenopausal women without subgingival calculus, whereas no significant association was identified in postmenopausal women with subgingival calculus.…”
Section: Discussionsupporting
confidence: 86%
“…However, the periodontal assessment in those studies was alveolar bone loss, and oral hygiene was not evaluated. The effect of oral hygiene on the association between BMD and periodontal disease was evaluated in previous cross‐sectional studies with diverse findings . Similar to our findings, the Buffalo Women's Health Initiative Observational Study reported a significant association between skeletal BMD and the mean CAL in postmenopausal women without subgingival calculus, whereas no significant association was identified in postmenopausal women with subgingival calculus.…”
Section: Discussionsupporting
confidence: 86%
“…Earlier studies reported a significant difference in periodontal depth between normal BMD and osteoporosis, which is similar to the present study . In another study, probing depth was significantly higher in the postmenopausal group (90% were osteopenic or osteoporotic) compared to premenopausal group (all were normal) .…”
Section: Discussionsupporting
confidence: 91%
“…Additional clinical information such as probing pocket depth would have been useful in determining more accurately which participants had CP. Nonetheless, we attempted to take this into account by using a combination of diagnosis and CP‐related treatment codes, an operational definition that was used in previous reports . Second, we did not have access to medical chart records related to dementia but rather had to rely on diagnosis codes and drug prescription records.…”
Section: Discussionmentioning
confidence: 99%